Crash into you - McGarry, Katie (Don Mills, Ontario, Canada : Harlequin Teen, 2013)
Rachel Young keeps secrets from her wealthy parents and overbearing brothers-- and she's just added two more to the list. One involves racing strangers down dark country roads in her Mustang GT. The other? Seventeen-year-old Isaiah Walker-- a guy she has no business even talking to.
Keywords: Teenagers -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Secrecy -- Juvenile fiction; Automobile racing -- Juvenile fiction; Teenagers -- Fiction; Man-woman relationships -- Fiction; Secrets -- Fiction; Automobile racing -- Fiction; Love -- Fiction; Love stories